Prevalence, management, and outcomes of haemorrhagic events in left ventricular assist device recipients - Laetitia Pourtau; Maxime Beneyto; Jean Porterie; Jerome Roncalli; Montse Massot; Caroline Biendel; Pauline Fournier; Romain Itier; Michel Galinier; Olivier Lairez; Clement Delmas (ESC Heart Failure)
Abstract Aims Left ventricular assist devices (LVADs) have reduced the mortality of patients with advanced heart failure both as bridge‐to‐transplant and as destination therapy. However, LVADs are associated with various complications, including bleedings, which affect the prognosis. The aim of the study was to explore the prevalence, management, and outcomes of haemorrhagic adverse events in LVAD recipients. Methods and results We conducted a retrospective, single‐centre, cohort study including all patients who received an LVAD from January 2008 to December 2019 in our tertiary centre (Rangueil University Hospital, Toulouse, France). Bleeding events, death, and heart transplantation were collected from electronic medical files. Eighty‐eight patients were included, and 43 (49%) presented at least one bleeding event. Gastrointestinal (GI) bleeding was the most frequent (n = 21, 24%), followed by epistaxis (n = 12, 14%) and intracranial haemorrhage (n = 9, 10%). Bleeding events were associated with increased mortality [hazard ratio (HR) 3.8, 95% confidence interval (CI) 1.5–9.3, P < 0.01], particularly in case of intracranial haemorrhage (HR 14.6, 95% CI 4.2–51.1, P < 0.0001). GI bleedings were associated with a trend towards increased mortality (HR 3.0, 95% CI 0.9–9.3, P = 0.05). Each bleeding episode multiplied the risk of death by 1.8 (95% CI 1.2–2.7, P < 0.01). Finally, only early bleedings (<9 months post‐implantation) had an impact on mortality (HR 4.2, 95% CI 1.6–11.1, P < 0.01). Therapeutic management was mainly based on temporary interruption of anticoagulation and permanent interruption of antiplatelet therapy. Invasive management was rarely performed. Conclusions Haemorrhagic events in LVAD recipients are frequent and associated with increased mortality. GI bleedings are the most frequent, and intracranial haemorrhages the most associated with mortality. Management remains empirical requiring more research.